Development of Guidelines for Beginning Counting Assessment Learning Problems of Elementary School Age - Atma Widia; Ranti Novianti; Salma Nadiyah; Fadly Halim Hutasuhut (International Inclusion Development and Cooperation, 2022)
Based on the results of the literature study, it was found that there were not a few children who had problems in calculating the beginning or often referred to as learning problems. This study uses a qualitative approach, and uses the library research method by looking at data based on article sources, handbook journals and research that has been carried out by previous research. The data collection technique used is literature study. The research was conducted with the aim of compiling guidelines for initial numeracy assessment for children with learning problems of elementary school age. This study produces a product in the form of a preliminary numeracy assessment guide for children with learning problems of elementary school age who have gone through the validation or expert judgment stage with the conclusion that the initial numeracy assessment guideline for children with learning problems of primary school age is appropriate to use. Assessment activities are activities to determine the abilities, barriers and needs of children so that it can be seen which learning programs are deemed appropriate to be given to children. The initial numeracy assessment guideline is appropriate for parents or teachers to use at school to determine the ability of the child's early numeracy barriers and needs.